SQL Cookbook, 2nd Edition - Molinaro, Anthony; De Graaf, Robert (O'Reilly Media, Inc., 2020)
You may know SQL basics, but are you taking advantage of its expressive power? The new edition of this cookbook applies a highly practical approach to Structured Query Language (SQL) so you can create and manipulate large stores of data. Based on real-world examples, this updated book provides a framework to help you construct solutions and executable examples in several flavors of SQL-including Oracle, DB2, SQL Server, MySQL, and PostgreSQL. SQL programmers, analysts, data scientists, database administrators (DBAs)-and even relatively casual SQL users-will find SQL Cookbook to be a valuable problem-solving guide for everyday issues. No other resource offers recipes in this unique format to help you tackle nagging day-to-day conundrums with SQL. The second edition includes: Fully revised recipes that recognize the greater adoption of window functions in various SQL implementations Additional recipes to take advantage of the widespread adoption of common table expressions for more readable, easier to implement solutions Brand-new recipes to make SQL more useful for people, such as data scientists, who aren't database experts Up-to-date SQL recipes throughout the book that cover the basics.
Online resource; Title from title page (viewed December 25, 2020)